Implementasi Kebijakan Penataan Pedagang Kaki Lima Sebagai Upaya Peningkatan Daya Saing Usaha di Kabupaten Bangkalan - Ilvia Nurrohmah Maulida; Yusuf Hariyoko; Indah Murti (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Bangkalan Regency, located in the province of East Java, Indonesia, is known for its vibrant street vendor culture, which plays an important role in the local economy. However, despite their cultural and economic significance, street vendors in Bangkalan face various challenges that hinder their competitiveness and sustainability. This research was designed to describe the six variables of Donald Van Metter and Carl Van Horn's model in the implementation of the Street Vendor Arrangement policy as an effort to increase business competitiveness in Bangkalan district. This type of research is a qualitative descriptive study. There is Donald Van Metter and Carl Van Horn's variable model, standard; objective; and policy objectives, resources, characteristics of the implementing organization, implementing attitudes, communication between organizations, socio-economic and political environment. This policy is seen from the six variables in the Donald Van Metter and Carl Van Horn Model in the implementation of the Street Vendor Arrangement policy as an effort to increase business competitiveness in Bangkalan district which has been implemented. However, there are obstacles faced by local governments in implementing street vendor control policies, including the government's low motivation in implementing policy outreach, the lack of strategic relocation solutions, and the existence of pressure groups, namely street vendors in Bangkalan district, who violate government regulations.